RANK ligand, jeho role při vzniku CTIBL a význam jeho inhibice - Študent, V (Česká urologie, 2011)
Androgen deprivation therapy is standard first line therapy in prostate cancer patients. It is used for its proven anticancer efficacy, has however a negative impact on bone heatlh. Osteoclasts are bone cells responsible for osteoresorption. Key mediator for their differentiation, maturation, activity and survival is the RANKL (receptor activator of nuclear factor kappa B ligand) produced by osteoblasts. Osteoprotegerin is soluble receptor binding RANKL. Hormon ablation decreases estrogen level thus causing cancer treatment bone loss (CTIBL) by down regulation of protegerin production. Relative over-abundance of RANKL leads to decreased bone mineral density (BMD) which predispones patients for pathological fractures. New therapeutic option use the mechanism of RANKL inhibition.